Macromolecular Brushes by Combination of Ring-Opening and Ring-Opening Metathesis Polymerization. Synthesis, Self-Assembly, Thermodynamics, and Dynamics - Nikovia, Christiana; Theodoridis, Lazaros; Alexandris, Stelios; Bilalis, Panayiotis; Hadjichristidis, Nikos; Floudas, George; Pitsikalis, Marinos (Macromolecules, 2018)
Statistical and block copolymerization of poly(l-lactide) (PLLA) and poly(ε-caprolactone) (PCL) macromonomers having an end norbornenyl group was performed via ring-opening metathesis polymerization (ROMP) to produce the corresponding statistical and block brush copolymers consisting of PLLA and PCL side chains on a polynorbornene (PNBE) backbone. The molecular characteristics of the macromolecular brushes were determined by 1H NMR spectroscopy and size exclusion chromatography equipped with various detectors. These complex topologies allow addressing important questions on the physics of semicrystalline polymers. These include the role of (i) a doubly grafted PCL or PLLA chain on a NBE moiety (in the macromonomers) and the role of (ii) brush architecture on the crystallization behavior and dynamics of block and statistical copolymers. Significant differences were found between the macromonomers and the corresponding brush copolymers at the crystalline lamellar and spherulitic superstructure levels. In the symmetric brush copolymers, two discrete crystalline lamellae corresponding to PLLA and PCL crystals were formed with that of PNBE–PLLA being thicker as compared to PNBE–PCL. Crystallization of the minority component (PCL) was totally suppressed in the brush copolymers (statistical and block) with asymmetric composition (PLLA–PCL 80–20). These results suggest strong restrictions in the crystallization of the block with the lower crystallization temperature (PCL) as well as confinement effects in the double macromonomers, resulting in lower crystallization and melting temperatures. At the level of spherulitic superstructure, NBE–PCL and NBE–(PCL)2 form the usual spherulites with growth rates that are dominated by the segmental dynamics. On the other hand, NBE–PLLA forms normal spherulites at low temperatures that transform to banded spherulites at higher temperatures. NBE–(PLLA)2 forms banded spherulites over the whole temperature range. A common feature of PLLA macromonomers is the nearly temperature-independent growth rates around 30 K, reflecting a property of the segmental dynamics. In the brush copolymers with symmetric composition both PLLA (in banded spherulites) and PCL could crystallize. PCL crystallization initiated at the same nucleation sites that crystallized PLLA at higher temperatures.